Looking on the heart ; v. 2 expositions of the book of 1 Samuel - Davis, Dale Ralph (Grand Rapids, MI Baker, 1994)
Contents : v.2 : 1 Samuel 15-31. Includes bibliographical references.
Keywords: Bible. O.T. Samuel, 1st, XV-XXXI -- commentaries